Pengembangan Ekonomi Lokal di Desa Raut Bosi : Peran Sektor Pertanian dalam Meningkatkan Kesejahteraan Masyarakat - Sindi Claudia Br. Pinayungan; Lastri Lastri; Vincentius Mikael Lumbantoruan; Christina Uliarta Gultom; Restu S.T Sihombing; Satrio Theophilus Telaumbanua (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service project focuses on evaluating the potential and challenges of local economic development in Raut Bosi Village, with a special emphasis on the agricultural sector, which is the primary economic driver in the village. It also explores the roles of the community, private sector, and government in supporting local economic development. By adopting a descriptive qualitative approach and utilizing SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, data for this study was gathered through interviews, field observations, and documentation during the period of February 19–27, 2025. The findings indicate that the traditional agricultural systems, such as Marsidapari, hold significant social and ecological value. These systems contribute not only to the livelihood of the local community but also to the preservation of local identity and culture. Despite this, the agricultural sector in Raut Bosi faces a series of structural challenges, particularly in terms of access to modern agricultural technologies, reliable market access, and supportive government policies. These challenges hinder the sector’s potential to grow and become more sustainable in the long term. In light of these challenges, this project recommends a strategy that combines local wisdom with sustainable agricultural innovations. Such a strategy would involve integrating modern techniques that enhance productivity while respecting traditional farming practices. Additionally, fostering collaboration among local stakeholders—such as farmers, the private sector, and government agencies—can create a supportive ecosystem for agricultural development. The academic contribution of this community service lies in its formulation of a local economic development model that aligns with the unique characteristics of Raut Bosi. This model emphasizes the value of local culture and traditions while promoting sustainable economic growth.